Virtual Reality – revisiting taxonomies for mixed reality performance - Gomes, Clara (European Public & Social Innovation Review, 2025)
Introduction: During the pandemic, the arts adapted to the virtual possibilities of the internet, with mixed reality gaining attention once again. This article revisits the concept of mixed reality, particularly in the context of digital performance theory, specifically cyberformance. Methodology: The study employed bibliographic review, critical analysis, and observational research of artistic cases (the researcher as artist) to test the hypothesis that cyberformance inherently embodies mixed reality by merging physical and virtual spaces, even in online presentations. Results: The study explored Benford and Giannachi's view on mixed reality performance (MRP), revisited Milgrim and Koshino's Virtuality Continuum, and examined digital performance models proposed by Birringer, Causey, and Schrum. Taxonomies for understanding cyberformance were analyzed, highlighting their limitations in capturing its fluid and evolving nature. Discussion and Conclusions: While taxonomies offer useful frameworks for cyberformance, they often fail to fully encapsulate its evolving, fluid nature. The study emphasizes that the significance of cyberformance goes beyond traditional categories, making it a complex and dynamic field.